Uncovering the needs for a hybridized interaction design model for sign language learning through experts’ feedback - Aziz, Nurulnadwan; Che Omar, Azizah; Abdul Mutalib, Ariffin; Ahmad, Siti Zulaiha; Muin, Mohd Adib; Annamalai, Subashini (IOP Publishing, 2020)
Nielsen's and Molich's design guidelines have been famously adapted in studies related to the design of interactive products, including for learning environment, and for hearing-impaired learners. In current situation, the learning materials for hearing-impaired learners are lacking in terms of positive interactions that promote two-way communication, partly because they do not apply appropriate design principles appropriately for the users. This affects their stimulation in learning activities. Hence, this paper aims at uncovering the current design principles applied in learning materials for learning sign language for the hearing-impaired learners. Besides an elicitation of literature, a semi-structured interview with the experts in hearing-impaired curricula has been carried out. It reveals that a study needs to urgently be carried out in proposing a heuristics design model that is specifically able to evoke the positive learning experience.